Pathophysiology and management of gustatory rhinitis - Shally Adhina Putri; Nina Irawati (PERHATI-KL, 2020)
ABSTRACTBackground: Gustatory rhinitis is a syndrome that causes symptoms of annoying rhinorrhea, occurring immediately after consuming solid or liquid foods which are hot and /or spicy. Usually starts within a few minutes after the ingestion of the foods involved, and is not associated with itching, sneezing, nasal congestion or facial pain. Purpose: To discuss the pathophysiology and proper management of gustatory rhinitis. Literature Review: Recent studies suggest that gustatory rhinitis is likely associated with phenomenon of neurogenic inflammation. The ingestion of spicy foods caused the stimulation of trigeminal sensory nerve endings located in the upper part of the aerodigestive track. Sensory nerve stimulation seems to be correlated with an activation of post ganglionic cholinergic muscarinic parasympathetic fibers and sensitive to atropine. Conclusion: The initial management of gustatory rhinitis is avoiding the trigger foods. Using combination of topical steroid and anticholinergic intranasal had been proven more effective to treat the rhinorrhea caused by gustatory rhinitis than administration of single drug. ABSTRAKLatar belakang: Rinitis gustatori adalah sindroma yang menimbulkan gejala rinore yang mengganggu, sesaat setelah mengonsumsi makanan padat atau cair, yang bersifat pedas dan/atau berempah. Biasanya dimulai dalam beberapa menit setelah menelan makanan tersebut, dan tidak disertai dengan gatal, bersin, hidung tersumbat atau nyeri wajah. Tujuan: Untuk membahas patofisiologi dan tatalaksana yang tepat pada rinitis gustatori. Tinjauan Pustaka: Sejumlah studi terbaru mendapatkan rinitis gustatori berkaitan dengan fenomena inflamasi neurogenik. Proses menelan makanan pedas dapat menyebabkan stimulasi ujung saraf sensorik trigeminal yang terletak di jalur aerodigestif bagian atas. Stimulasi saraf sensorik tersebut berkaitan dengan pengaktifan serabut saraf parasimpatik muskarinik kolinergik post ganglion yang sensitif terhadap atropin. Kesimpulan: Tatalaksana awal yang dapat dilakukan untuk mengatasi rinitis gustatori adalah menghindari makanan pemicu. Kombinasi penggunaan antikolinergik intranasal dan steroid topikal, secara profilaksis atau sebagai terapi telah terbukti lebih efektif untuk mengatasi rinore akibat rinitis gustatori dibandingkan pemberian masing- masing obat tersendiri.